Regulation: Managing the Antinomies of Economic Vice and Virtue. (December 2017) - Picciotto, Sol
In the quarter-century that Social & Legal Studies has been published, regulation has emerged as a new, and for many exciting, interdisciplinary field. The concept itself requires a wider view of normativity than the narrow positivist one of law as command. It is certainly protean, ranging over many fundamental questions about the changing nature of the public sphere of politics and the state, and its interactions with the 'private' sphere of economic activity and social relations, as well as the mediation of these interactions, especially through law. This survey aims to outline and evaluate some of the main contours of the field as it has developed in this recent period, focusing on the regulation of economic activity. Regulation is seen as having emerged with the withdrawal by governments from direct provision of many economic and social services, to be replaced by corporatist bureaucracies and quasi-public agencies managing the complex public–private interactions of financialized capitalism. The arguments for 'smart' regulation have, in an era fixated on neo-liberalism, generally legitimized delegation of responsibility to big business. Its advocates, having been drawn into policy fields, have perhaps too often lost their critical edge, and allowed it to become instrumentalized, reflecting the technicist character of its practice.